Spatiotemporal variability of phytoplankton communities in the euphotic layers of a tropical caldera lake (Lake Taal, Batangas, Philippines) - YITZHAK UZI SHALOM P. INOG; CHRISTON JAIRUS M. RACOMA; JEAN-MATTHEW B. BATE; GARRY A. BENICO; DINO T. TORDESILLAS (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Inog YUSP, Racoma CJM, Bate J-MB, Benico GA, Tordesillas DT. 2025. Spatiotemporal variability of phytoplankton communities in the euphotic layers of a tropical caldera lake (Lake Taal, Batangas, Philippines). Biodiversitas 26: 3302-3314. Lake Taal in Batangas, Philippines, is an ecologically and economically significant protected area that supports unique biodiversity. Monsoonal patterns and trophic status play a critical role in shaping the lake, however, their effect on the phytoplankton communities in tropical lakes is poorly understood. To address this gap, a spatiotemporal assessment was conducted to examine the diversity and distribution of phytoplankton communities in the euphotic layers of Lake Taal. Water samples across euphotic layers were collected from north (aquaculture) and south (non-aquaculture) basins during three monsoonal events in 2024 (February (northeast monsoon), August (southeast monsoon), and October (intermonsoon)) at varying depths within the euphotic layer and filtered using a 20-µm plankton net. A total of 40 phytoplankton species, representing five classes, with Cyanophyceae (70.78%) dominating the entire lake in density, indicating eutrophic conditions. Phytoplankton abundance showed significant variation across monsoons and basins, while remaining statistically uniform across the euphotic layers, inferring minimal vertical stratification in density. Aquaculture areas had higher phytoplankton density than non-aquaculture areas. Furthermore, the northeast monsoon had the highest phytoplankton density dominated by Microcystis aeruginosa, a harmful algal bloom former, shifting to Cyanocatena imperfecta during the southwest to October intermonsoon period. Diversity indices revealed a moderate diversity with high dominance, and ordination methods revealed monsoon-driven events heavily impacted the phytoplankton community structure of the lake. Canonical Correspondence Analysis (CCA) showed that water temperature, turbidity, and dissolved oxygen are key environmental factors shaping phytoplankton community structure, influencing species succession and distribution via light penetration and photosynthesis efficiency. The findings underscore the effects of eutrophication and highlight the need for continuous monitoring and seasonally adaptive environmental management strategies in tropical eutrophic lakes.